Emergenza sull’Himalaya - Stenmark, John (GEOmedia, 2016)
Following April 2015's major earthquake in Nepal, massive efforts focused on providing aid to victims and survivors. Working behind the scenes, a small team of scientists scrambled to secure perishable data that could both explain how the quake occurred and help people prepare for the next one.